World Economic and Financial Surveys, 1993 : International Capital Markets: Part I. (World Economic and Financial Surveys; World Economic and Financial Surveys ;, 1993)
This paper examines the implications of the growth and integration of international capital markets for the management of exchange rates, with particular attention to the inferences that can be drawn from the currency turmoil that shook the European Monetary System (EMS) last fall and winter. The resources available to the private sector for taking positions in the forex market are now much larger than even those of the Group of Ten central banks. When private markets, led by the increasing financial muscle of institutional investors, reach the concerted view (rightly or wrongly) that the risk/return outlook for a particular currency has deteriorated significantly, the defending central bank could be faced with a run that could easily amount to, say, USD 100-200 billion or more within a week. The range of private market participants involved in last fall's crisis in European currency markets was broad-encompassing banks, securities houses, institutional investors, hedge funds, and corporations. However that wide participation explains in part why the funds that flooded into central banks were so massive.